Upaya Meningkatkan Kedisiplinan dan Hasil Belajar Matematika Siswa Melalui Penggunaan Media Power Point Interaktif - Setya Pambudi; Shanta Rezkita; Endang Purwaningsih (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
The purpose of this research to describe the process of learning mathematics by using interactive power point media in fifth grade students of SD Negeri 1 Kebakalan Karanggayam Kebumen to improve student discipline and learning outcomes. This research was conducted in the fifth grade of SD Negeri 1 Kebakalan, Karanggayam District, Kebumen Regency. This type of research is Classroom Action Research. The subjects of this study were all the fifth grade students of SD Negeri 1 Kebakalan Karanggayam Kebumen totaling 26 students. Data collection techniques in this study used observation techniques, test techniques, field notes, and documentation. The results of this study indicate that through the use of interactive power point media can improve discipline and learning outcomes of mathematics, indicated by the average percentage of pre-action student discipline is 50%, the first cycle increases to 73%, and the second cycle increases again to 89%. The increase in student learning outcomes is indicated by an increase in the number of students who meet the KKM and an increase in the average score of students. In the pre-action, the percentage of completeness is 31%. At the end of the first cycle it increased to 58% and at the end of the second cycle it increased to 77%. Thus, mathematics teachers are expected to be able to use interactive power point media in teaching in order to get maximum results.